Inductance, Capacitance, Resonance and Time Constants - Basic Calculations - Prudhomme, William (McGraw-Hill's AccessEngineering., 2015)
Software simulation programs are generally used for modeling and designing complex electronic circuits and applications, but frequently only a basic calculation is needed to solve an immediate design problem or to calculate the value of a specific circuit element. This Excel workbook addresses this need by automating the calculation of over 34 basic electronics formulas for circuits involving capacitance, inductance, resonance, and/or time constants. The workbook includes worksheets on: 1. Inductance: Calculation of series and parallel inductance, energy stored in an inductor, series and parallel inductive reactance, frequency, inductance, and inductive reactance when the frequency and inductance are known. 2. Capacitance: Calculation of series and parallel capacitance, charge and energy stored in a capacitor, series and parallel capacitive reactance, frequency, capacitance, and capacitive reactance. 3. Resonance: Calculation of capacitance, inductance, resonant frequency, capacitive reactance, inductive reactance, Q-factor, and bandwidth for series and parallel resonant circuits. 4. Time Constants: Calculation of time constants, resistance, capacitance, and inductance for series RC and L/R circuits.